Research on the Same Frequency Interference on EGSM Uplink Signal from CDMA Downlink Signal - Fangyuan Lei; Gang Lei (Dianxin kexue)
The major factor affecting the EGSM network performance is the same frequency external interference from CDMA of other country in the border areas. A case which EGSM operator subject to a wide range of strong external interference by same frequency of neighbor country CDMA operators was analyzed, then a solution to reduce this external interference was proposed. Firstly, with KPI statistical and DT test analyze, the external interference source was located, and the intensity and scope of the effects also was confirmed. Then, using the rural Hata propagation model theoretically, the impact and scope of CDMA interference was analyzed; combined with the respiratory effects of CDMA network, the differences between day and night EGSM external interference were analyzed. Final, the solution was proposed, which use deviate cell of border to carry traffic, use the clean frequency band to plan or use the 1 800 MHz frequency to carry the traffic. Those solution weakened external interference, the KPI and user effecting of EGSM network has achieved good results.